2001
DOI: 10.1161/hc4201.097136
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Heterogeneity of Calcium Transient Alternans During the Early Phase of Myocardial Ischemia in the Blood-Perfused Rabbit Heart

Abstract: Background-Optical mapping of cytosolic calcium transients in intact mammalian hearts is now possible using long-wavelength [Ca 2ϩ ] i indicators. We propose that beat-to-beat [Ca 2ϩ ] i transient alternans during ischemia may lead to spatial and temporal heterogeneity of calcium-activated membrane currents. Methods and Results-To test this hypothesis, isolated rabbit hearts were loaded with the fluorescent [Ca 2ϩ ] i indicator, rhod-2 AM, and imaged at 300 frames/sec during blood-perfused ischemic trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
88
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(94 citation statements)
references
References 21 publications
5
88
1
Order By: Relevance
“…17,24,28,29 Recently, regions comprising several cells have been found to alternate in phase but out of phase with other regions. 30 The present study shows that tetracaine or acidification can result in a small degree of alternans at the whole cell level (Figures 2 and 6). One novel result is that, under these conditions, alternating Ca 2ϩ release is more obvious at the subcellular level where regions of the order of tens of microns alternate out of phase with each other.…”
Section: Relationship Between Subcellular and Cellular Alternanssupporting
confidence: 53%
“…17,24,28,29 Recently, regions comprising several cells have been found to alternate in phase but out of phase with other regions. 30 The present study shows that tetracaine or acidification can result in a small degree of alternans at the whole cell level (Figures 2 and 6). One novel result is that, under these conditions, alternating Ca 2ϩ release is more obvious at the subcellular level where regions of the order of tens of microns alternate out of phase with each other.…”
Section: Relationship Between Subcellular and Cellular Alternanssupporting
confidence: 53%
“…The experiments reported here utilized the same experimental model and recording apparatus used by Qian et al (30) alternans was confined to specific regions of the heart surface, and multiple regions, which were out of phase and separated by a boundary, could be present in the same heart. Circumscribed regions of [Ca 2ϩ ] i transient alternans were as small as 5 mm and quantitative maps could be constructed using an alternans ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Thus it is likely that most or all of the hearts had regions where APD alternans was out of phase. Qian et al (30) found Ca 2ϩ transient alternans in each of the eight ischemic hearts studied with rhod-2, with regions where alternans was out of phase in six of the eight hearts. Because rhod-2 has a considerably better signal-to-noise ratio than di-4-ANEPPS, the ability to detect alternans and the completeness of the alternans maps would be better with rhod-2.…”
Section: Action Potential Propagation Under Control Conditions and Dumentioning
confidence: 94%
See 1 more Smart Citation
“…The use of absorption measurements at Rhod-2-sensitive wavelengths can be used to quantify relative levels of calcium [5,6]. There is growing interest in using Rhod-2 to measure calcium transients from the intact heart [5][6][7][21][22][23][24]. To decrease the influence of motion, in this study we have developed a technique to filter motion artifacts from the fluorescence signal in the frequency domain using the shift theorem of Fourier analysis which is independent of the time-shift error that may occur in the motion reference signal.…”
Section: Introductionmentioning
confidence: 99%